SheMurenga: The Zimbabwean Women's Movement 1995-2000 - Essof, Shereen (Book collections on Project MUSE., 2013)
This book demonstrates the place of women's movements during a defining period of contemporary Zimbabwe. The government of Robert Mugabe may have been as firmly in power in 2000 as it was in 1995, but the intervening years saw severe economic crisis, mass strikes and protests, the start of land occupations, intervention in the war in the DRC, and the rise of the opposition Movement for Democratic Change. The author shows how Zimbabwean women crafted responses to these and other events, and aimed for a feminist agenda that would prioritise the interests of the rural and urban poor. Rejecting both the strictures of patriarchy and the orthodoxies of established feminism, the author demands that Zimbabwe's women be heard in their own voices and in their own contexts. In doing so, this book combines scholarly integrity with a wild, joyous cry for liberation.